IMPLEMENTASI GERAKAN LITERASI SEKOLAH (GLS) DALAM MEMPERKUAT NILAI BUDI PEKERTI PESERTA DIDIK - Agung Tri Kurniawan; Sastra Juanda; Ikman Nur Rahman (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This research aimed to provide an overview of the implementation of the School Literacy Movement (GLS) in strengthening students' character values at SDN Anyar 3. The SLM was actually formed in 2015, and it is also stated in Permendikbud No. 23 of 2015 concerning Character Growth. Therefore, schools in Indonesia began to implement SLM program in addition to fostering a literacy culture and cultivating students' character values. In addition, the GLS program itself has guidelines so that schools implement it as expected by the government. SLM was conducted outside of learning to attract students' attention to be engaged in literacy. That way students can understand the value contained in the reading book so that students are stimulated to carry out the values of character in reading books in everyday life.